2001
DOI: 10.1037/0893-164x.15.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of expressed and received violence across relationship types among men and women substance abusers.

Abstract: This study examined expressed and received violence among men and women in substance abuse treatment. Rates of past-year partner violence (PV) did not differ by gender, although men reported markedly higher rates of nonpartner violence (NPV). Compared with PV, NPV was associated with more demographic and background factors (e.g., childhood aggression and conduct problems, family history of violence). The most consistent correlates of violence across relationship types were age, minority status, drug-related co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
115
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 56 publications
14
115
2
3
Order By: Relevance
“…Similar proportions of men and women reported experiencing a recent violent attack at baseline (21% vs. 22%) and over the follow-up period (50% vs. 43%). These results are consistent with previous studies that have observed comparable overall rates of received violence among drug-using men and women (Chermack et al, 2001;Finlinson et al, 2003). In longitudinal multivariate analyses examining the risk factors associated with received violence, many similarities between sexes were observed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar proportions of men and women reported experiencing a recent violent attack at baseline (21% vs. 22%) and over the follow-up period (50% vs. 43%). These results are consistent with previous studies that have observed comparable overall rates of received violence among drug-using men and women (Chermack et al, 2001;Finlinson et al, 2003). In longitudinal multivariate analyses examining the risk factors associated with received violence, many similarities between sexes were observed.…”
Section: Discussionsupporting
confidence: 91%
“…One study examining received violence in a sample of individuals participating in substance abuse treatment found no gender difference in the proportion of participants reporting violence from partners (61% versus 65% among men and women, respectively), while males reported higher rates of violence from non-partners (75% versus 45% among men and women, respectively) (Chermack et al, 2001). Although the expression of violence has traditionally been associated with masculine gender roles, which in turn are at least partially responsible for the linking of partner violence perpetuation and sexual risk behaviours (Santana et al, 2006), received violence among male IDU is also common and likely underreported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In a substance abuse treatment sample, 61 % of men and 65 % of women reported being the victim of physical partner violence, and 75 % of men and 45 % of women reported physical victimization from a person other than an intimate partner in the past 12 months. 3 The HIV risk behaviors of an individual's sexual partners, in addition to condom use, have significant epidemiological implications for the Turner, Rivera, and Lewis are with the …”
mentioning
confidence: 99%
“…4 Physical victimization has been linked to high-risk sexual partnerships in women like having an HIV-positive sexual partner and other risk factors for HIV including having unprotected sex and having an STI. 5,6 Although men are more likely to be victims of any kind of violence, 3,7 the few studies examining physical victimization and sexual risk behavior among men have mostly focused on intimate partner violence (IPV) among men who have sex with men (MSM). [8][9][10][11] Fewer studies have examined the association between physical victimization and sexual risk behavior in heterosexual men or illicit drug users.…”
mentioning
confidence: 99%